2015
DOI: 10.4049/jimmunol.1401644
|View full text |Cite
|
Sign up to set email alerts
|

OX40- and CD27-Mediated Costimulation Synergizes with Anti–PD-L1 Blockade by Forcing Exhausted CD8+ T Cells To Exit Quiescence

Abstract: Exhaustion of chronically stimulated CD8+ T cells is a significant obstacle to immune control of chronic infections or tumors. Although co-inhibitory checkpoint blockade with anti-programmed death-ligand 1 (PD-L1) antibody can restore functions to exhausted T cell populations, recovery is often incomplete and dependent upon the pool size of a quiescent T-bethigh subset that express lower levels of PD-1. In a model where unhelped, HY-specific CD8+ T cells gradually lose function following transfer to male BMT r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 44 publications
2
52
0
1
Order By: Relevance
“…Combining agents that target LAG-3, IDO, ICOS, TIM-3, 4-1BB, OX40, and CD27 with anti-PD-1/PD-L has been supported by preclinical models (53)(54)(55)(56)(57)(58)(59)(60), and many of these elements (e.g., LAG-3, TIM-3, IDO, and so forth) are currently being tested in clinical trials (https://clinicaltrials. gov; NCT01968109, NCT02608268, NCT02559492).…”
Section: Discussionmentioning
confidence: 99%
“…Combining agents that target LAG-3, IDO, ICOS, TIM-3, 4-1BB, OX40, and CD27 with anti-PD-1/PD-L has been supported by preclinical models (53)(54)(55)(56)(57)(58)(59)(60), and many of these elements (e.g., LAG-3, TIM-3, IDO, and so forth) are currently being tested in clinical trials (https://clinicaltrials. gov; NCT01968109, NCT02608268, NCT02559492).…”
Section: Discussionmentioning
confidence: 99%
“…The 1F5 antibody is currently in phase I trial for the treatment of hematologic malignancies and solid tumors. Based on the coexpression of CD27 and PD1 on TIL, combining agonistic CD27 antibody with a checkpoint blockade targeting the PD1/PD-L1 axis might be of further interest, because preclinical studies have shown a synergistic effect of combinatorial antibody treatment (28). Currently, also other treatment strategies for HGSC are being explored including strategies targeting angiogenesis (e.g., bevacizumab) and PARP inhibitors in tumors with alterations in the homologous recombination repair pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with data from chronic viral infections where PD-1 blockade could only rescue T-cell subsets with intermediate but not high levels of PD-1 expression. 37 Approaches combining blockade of the PD-1/PD-L1 axis with agonistic antibodies to either OX40 or CD27 have been shown to temporarily restore functionality to exhausted T-cells in a murine bone marrow transplantation model 48 thereby leading to the loss of Tbet hi PD-1 int T-cells and contraction of the effector pool capable to sustain the immune response. Similarly, administration of low-dose IL-2 combined with PD-L1 blockade has been demonstrated to decrease inhibitory receptor expression and viral load in a chronic murine LCMV model as IL-2 treatment may foster the generation of a pool of CD44 hi PD-1 int T-cells that are more responsive to PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%